2007
DOI: 10.1111/j.1365-2133.2007.07924.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic alterations in the differential diagnosis of malignant melanoma and spitzoid lesion

Abstract: Genetic and epigenetic analyses may be useful as an additional diagnostic tool to distinguish between melanoma and Spitz naevus, and may help to define subgroups in atypical Spitz tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 39 publications
6
67
2
Order By: Relevance
“…A limited number of studies have examined BRAF mutations in AST, and only one study reported finding a BRAF mutation in AST [25][26][27]. Mutations in NRAS (neuroblastoma RAS viral [v-ras] oncogene homolog) have also been reported in melanoma [25,26,28], but not in conventional Spitz nevi [25,26,28]. The inconsistencies between published studies may be related to a lack of consensus among dermatopathologists on histologic criteria used in the diagnosis of spitzoid melanocytic lesions [13].…”
Section: Braf/nrasmentioning
confidence: 88%
See 2 more Smart Citations
“…A limited number of studies have examined BRAF mutations in AST, and only one study reported finding a BRAF mutation in AST [25][26][27]. Mutations in NRAS (neuroblastoma RAS viral [v-ras] oncogene homolog) have also been reported in melanoma [25,26,28], but not in conventional Spitz nevi [25,26,28]. The inconsistencies between published studies may be related to a lack of consensus among dermatopathologists on histologic criteria used in the diagnosis of spitzoid melanocytic lesions [13].…”
Section: Braf/nrasmentioning
confidence: 88%
“…However, when the spectrum of spitzoid lesions is expanded to include unusual or atypical variants, such as spitzoid dysplastic nevi or Reed's nevi, the incidence of BRAF mutations is increased [27][28][29]. A limited number of studies have examined BRAF mutations in AST, and only one study reported finding a BRAF mutation in AST [25][26][27]. Mutations in NRAS (neuroblastoma RAS viral [v-ras] oncogene homolog) have also been reported in melanoma [25,26,28], but not in conventional Spitz nevi [25,26,28].…”
Section: Braf/nrasmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, investigation of key molecular aberrations in AST, such as mutations of the HRAS gene, have suggested that these lesions may merely represent a group of Spitz nevi and Spitzoid melanomas that are unclassifiable by light microscopy and not in fact genetically distinct entities [2]. This is a position that has been championed by Ackerman and colleagues for some time and is analogous to the viewpoint that 'classical' atypical nevi are a mixture of benign nevi and early melanomas, rather than precursors of melanomas per se [5][6][7][8].…”
Section: Expert Commentarymentioning
confidence: 98%
“…[15][16][17][18][19] This is in contrast to all spitzoid melanomas and conventional melanomas that have been analyzed to date, in which HRAS mutations are rare. 17,19,20 In addition, BRAF and NRAS mutations are uncommon in Spitz nevi, whereas they are common in melanomas. 21 Thus the presence of an HRAS mutation in a melanocytic neoplasm with Spitzoid morphology appears to favor the diagnosis of Spitz nevus, rather than a Spitzoid melanoma.…”
mentioning
confidence: 99%